2015
DOI: 10.4149/av_2015_03_257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ORF119 gene deletion on the replication and virulence of orf virus

Abstract: Summary. -Orf is a severe infectious disease of sheep and goats caused by orf virus (ORFV). To investigate the role of ORF119 gene of ORFV, we constructed ORFV with deleted ORF119 gene and LacZ as reporter gene (ORFV-Δ119-LacZ) via homologous recombination. The results showed that wild-type ORF-SHZ1 and ORFV-Δ119-LacZ deletion viruses replicated in Vero cells to similar titers. Relative transcriptional levels of virulence genes OVIFNR, GIF, VEGF and VIL-10 of ORFV-Δ119-LacZ deletion virus were slightly but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
4
2
Order By: Relevance
“…The mitochondrial protein coded by this gene was recently described as being capable of increasing cell apoptosis ( 44 , 45 ). Despite this finding, our observations and a previous report showed no phenotypic modification in the virus cycle regarding this gene deletion ( 46 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial protein coded by this gene was recently described as being capable of increasing cell apoptosis ( 44 , 45 ). Despite this finding, our observations and a previous report showed no phenotypic modification in the virus cycle regarding this gene deletion ( 46 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This deletion has been implied in cell apoptosis ( 44 , 45 ). Nevertheless, deletion of this gene did not affect the virus cycle and strain virulence ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…The attenuated phenotype of infection likely indicates improved host control of ORFV infection in the absence of ORFV119 ( S8 Fig ). Our results are at variance with a previous report where no differences in virulence and pathogenesis were observed between wild type and ORFV119 deletion viruses [ 71 ]. The discrepancy likely reflects differences in viral strains (IA82 vs SHZ1), extent of genomic deletion, and/or in vitro conditions for virus propagation.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, among the region of ORFs 118–120, the non-coding fragments are almost as long as the coding fragments ( Li et al, 2015 ). According to this insight, we speculate that these areas might be part of the coding regions in early stages of orf virus evolution ( Qiao et al, 2015 ). It is noteworthy, that ORFV119 was recently revealed able to inhibit NF-kappa B signaling through interaction with pRb ( Nagendraprabhu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 83%
“…However, further research is necessary to fully characterize this process, such as identifying the functional domain of ORFV119. Because some studies have reported that the deletion of the ORF119 gene had no significant effect on viral replication and virulence ( Qiao et al, 2015 ), future studies should include more ORFV strains, since virulence and genomes vary greatly among ORFV strains, viral recombination and subsequent in vivo experiments ( Delhon et al, 2004 ; Chi et al, 2015 ; Li et al, 2015 ). In addition, the relevance and interaction between regulation of NF-κB and regulation of apoptosis need to be explored further ( Nagendraprabhu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%